2018
DOI: 10.1590/1678-4162-9907
|View full text |Cite
|
Sign up to set email alerts
|

Indução do estro em cutias (Dasyprocta leporina) utilizando-se protocolos à base de prostaglandina isolada ou em associação com análogo de GnRH

Abstract: RESUMO Comparou-se a eficiência de protocolos para indução de estro em cutias. Em cinco fêmeas, foram administradas duas doses de cloprostenol (5µg) com intervalo de nove dias, via intraperitoneal; em outras cinco, administraram-se 30µg de análogo do hormônio liberador de gonadotrofinas (GnRH), via intravulvar, seguidos de 5µg de cloprostenol, via intraperitoneal, após sete dias e, após mais dois dias, nova dose do análogo de GnRH. A cada três dias, a ciclicidade reprodutiva dos animais foi monitorada, por mei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 18 publications
0
17
0
1
Order By: Relevance
“…In small rodentia, cloprostenol administered in higher dosis is efficient mainly if combined with progesterone, reaching up to 100% the response in oestrous synchronization and ovulation (Pallares & Gonzalez‐Bulnes, ). However, these results were not achieved in guinea pig (Grégoire et al, ) or agouti, showing limitations in oestrous induction (Peixoto et al, ). In addition, research has shown that the administered dose of this hormone may affect oestrous synchronization efficiency (Wei et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In small rodentia, cloprostenol administered in higher dosis is efficient mainly if combined with progesterone, reaching up to 100% the response in oestrous synchronization and ovulation (Pallares & Gonzalez‐Bulnes, ). However, these results were not achieved in guinea pig (Grégoire et al, ) or agouti, showing limitations in oestrous induction (Peixoto et al, ). In addition, research has shown that the administered dose of this hormone may affect oestrous synchronization efficiency (Wei et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Using only cloprostenol, estrus induction was verified in only 40% of females that manifested estrus signs and presented estrogen peak at 3 and 6 days after drug administration. However, combination therapy with both the hormones yielded estrus induction in 60% of animals, but 40% of the animals manifested estrus at day 4 and 20% at day 10 day after drug administration (Peixoto et al, 2018). Although these protocols promoted estrus induction, the authors do not suggest this method as an effective means to achieve synchronization of estrus induction in D. leporina.…”
Section: Art Applied To Female Agoutimentioning
confidence: 91%
“…Blood collection for hormonal analysis (serum estradiol and progesterone) could also aid in monitoring the estrous cycle [ 50 ]. This was performed using a 1 mL syringe to obtain blood via the cephalic or saphenous vein, which was placed in glass tubes and centrifuged in preparation for analysis via amplified electrochemiluminescence.…”
Section: Agouti ( Dasyprocta Leporina )mentioning
confidence: 99%
“…This was performed using a 1 mL syringe to obtain blood via the cephalic or saphenous vein, which was placed in glass tubes and centrifuged in preparation for analysis via amplified electrochemiluminescence. The animals that showed external signs of estrus had corresponding increases in their estrogen levels (22.4 pg/mL and 17.5 pg/mL) and low progesterone levels (3.5 ± 0.2 ng/mL) under the cloprostenol only method of estrus induction [ 50 ]. When cloprostenol was used in combination with a gonadotropin releasing hormone (GnRH) analogue, those that had external signs of estrus had corresponding increases in their estrogen levels (12.3 pg/mL, 8.5 pg/mL and 8.3 pg/mL) and low progesterone levels (2.5 ng/mL and 2.3 ng/mL) [ 50 ].…”
Section: Agouti ( Dasyprocta Leporina )mentioning
confidence: 99%
See 1 more Smart Citation